Examining the Association Between Quadriceps Strength and Cognitive Performance in the Elderly. Issue 32 (August 2015) - Chen, Wei-Liang; Peng, Tao-Chun; Sun, Yu-Shan; Yang, Hui-Fang; Liaw, Fang-Yih; Wu, Li-Wei; Chang, Yaw-Wen; Kao, Tung-Wei; Helen, Gharaei.
<x xml:space="preserve">Abstract</x> Abstract Emerging evidences showed impaired muscle strength was prevalent in older adults with mild cognition impairment or dementia. However, little was known about the role of quadriceps strength in the cognition decline among older population. The objective of our study was to investigate the relation between quadriceps strength and cognitive performance. Using data from the National Health and Nutrition Examination Survey (1999–2002), a total of 1799 participants aged ≥60 years were enrolled in the study. Every subject completed a household interview, digit symbol substitution test (DSST), physical performances, and a questionnaire regarding personal health. Estimation of relationship between quadriceps strength and cognition was using multiple linear regression and quartile-based analysis with an extended-model approach for covariates adjustment. In a model adjusted for demographics, chronic diseases, health behaviors, and levels of folate and vitamin B12, the level of quadriceps strength was significantly associated with the scores of DSST. The β coefficient interpreted as change of DSST scores for each Newton increment in quadriceps strength comparing participants in the highest quartile of quadriceps strength to those in the lowest quartile was 5.003 (95% confidence interval, 2.725–7.281, P < 0.001). The trends of incremental DSST score across increasing quartiles of quadriceps strength were statistically significant (all P for trend <0.001). Higher quadriceps strength was associated with better cognitive performance.